DNA methylation in a Scottish family multiply affected by bipolar disorder and major depressive disorder. Issue 1 (December 2016) - Walker, Rosie; Christoforou, Andrea; McCartney, Daniel; Morris, Stewart; Kennedy, Nicholas; Morten, Peter; Anderson, Susan; Torrance, Helen; Macdonald, Alix; Sussmann, Jessika; Whalley, Heather; Blackwood, Douglas; et al.
Abstract Background Bipolar disorder (BD) is a severe, familial psychiatric condition. Progress in understanding the aetiology of BD has been hampered by substantial phenotypic and genetic heterogeneity. We sought to mitigate these confounders by studying a multi-generational family multiply affected by BD and major depressive disorder (MDD), who carry an illness-linked haplotype on chromosome 4p. Within a family, aetiological heterogeneity is likely to be reduced, thus conferring greater power to detect illness-related changes. As accumulating evidence suggests that altered DNA methylation confers risk for BD and MDD, we compared genome-wide methylation between (i) affected carriers of the linked haplotype (ALH) and married-in controls (MIs), (ii) well unaffected haplotype carriers (ULH) and MI, (iii) ALH and ULH and (iv) all haplotype carriers (LH) and MI. Results Nominally significant differences in DNA methylation were observed in all comparisons, with differences withstanding correction for multiple testing when the ALH or LH group was compared to the MIs. In both comparisons, we observed increased methylation at a locus inFANCI, which was accompanied by increased FANCI expression in the ALH group.FANCI is part of the Fanconi anaemia complementation (FANC ) gene family, which are mutated in Fanconi anaemia and participate in DNA repair. Interestingly, severalFANC genes have been implicated in psychiatric disorders. Regional analyses of methylation differences identified loci implicated in psychiatric illness by genome-wide association studies, includingCACNB2 and the major histocompatibility complex. Gene ontology analysis revealed enrichment for methylation differences in neurologically relevant genes. Conclusions Our results highlight altered DNA methylation as a potential mechanism by which the linked haplotype might confer risk for mood disorders. Differences in the phenotypic outcome of haplotype carriers might, in part, arise from additional changes in DNA methylation that converge on neurologically important pathways. Further work is required to investigate the underlying mechanisms and functional consequences of the observed differences in methylation.